Child, mother and grandmother : intergenerational interaction in Finnish families - Hurme, Helena (1988)
This monograph reports the results of a Finnish study on intergenerational relations in the family. Is is based on semistructured interviews with 70 maternal grandmothers, their daughters and their 12-year-old grandchildren as well as on a larger questionnaire sample of these individuals. The study concerned several content areas: geographical distance between the generations, contacts between them, mutual aid and support, filial responsibility as well as affective relations. The grandmother role was also a topic of study. The results showed that the adult daughter almost invariably had loosened her ties with her mother and was less dependent on her than on her husband. The relationship between the adult generations is clearly an ambivalent one. In some families, the relationship was a very close one, but there were families where the relationship between the elderly mother and her adult daughter was almost nonexistent. The grandmother does not occupy a central role anymore in the life of a 12-year-old Finnish child. It is not that the relationship is a cold one; rather, the child seems to have so many other activities going on that the grandmother is not as important as before. This study did not support the contention that the oldest generation is left alone. The study also showed that Finnish daughters help their mothers independent of any emotional attachment to the mother. Help is determined solely by the mother's need for help. The results also partly supported the contention of earlier studies that the grandmother role is a roleless role. About a fifth of the grandmothers found it difficult to spontaneously define the main tasks of the grandmother.